Daily field checking list by Walter Rosene, April 11, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Boone, Ames and Little Wall Lake by Walter Rosene, April 11, 1937. Also notes he intended to take movies of the Pasque flowers but they were not in bloom yet. Plustek--flatbed